Reflections on the traditional teaching of Chemistry and a comparison between the teaching mechanisms: field demonstration and interactive simulation software (Research, Society and Development, 2019)
The teaching of chemistry in Brazil faces several problems in relation to apprenticeship. Then, one of the complications associated with this discipline is the scarcity of a laboratory environment maybe causes understanding problems. In fact, traditional education remains a majority with public schools, and contributes to cause a noticeable struggle in most students because sometimes chemistry is not clear and bring real life situations in them lessons. Hence, the present study aimed to brings reflection to learning difficulties in the contact between the students and chemistry. The association amid two of the main pedagogical teaching alternatives: Field Demonstration and ISS (Interactive Simulation Software). In this study was realized a survey of 10 articles that practiced a traditional teacher method, and the last most used forms in the last 4 years. The steps for choosing the works according to the method of exploratory study proposed by Antônio Carlos Gil in his book "How to Contribute Research Projects" were attend. Then, one possibility would show the almost inefficacy of the traditional system, where the teacher works limited with only a few resources of speech, paintbrush and blackboard, since a significant amount of dicents consider chemistry as mathematical science and tedious resource. The Field Demonstration allows a new point of view about chemical concepts applied to the daily life of society. Thus, generating interests about knowlement and appropriating knowledge related to industrial development. The use of ISS with students could have a understanding about some phenomenons of the microscopic world and assimilated. Hence, creating an association between theory and practice, all this in a simple and playful way. Thus, by the end of this evaluation is evident that the improvement of students performance and the quality of the teaching-learning process will only occur with the stimulation of new and attractive methodologies such as these, which enabled a complete development of the capacities of abstraction and correspondence of chemistry with the daily life of each individual student.